MEDIA PEMBELAJARAN DAN PERAN PENTINGNYA DALAM PENGAJARAN DAN PEMBELAJARAN BAHASA ARAB - Asni Furoidah (Al-Fusha : Arabic Language Education Journal, 2020)
Learning media plays an important role in learning Arabic. Learning media is not only good for children’s students, but also for adult students. The learning media used to convey the contents of teaching materials consisting of books, tape recorders, tapes, video cameras, video recorders, films, photos, pictures, graphics, television and computers are components of learning resources that contain teaching materials that can stimulate a person to learn. . The use of audio media in Arabic learning is very important in the material الاستماع, the teacher who delivers material using audio media will make it easier for students to hear every vocabulary that is pronounced correctly. The use of visual media can increase students ‹interest in writing (الأنشاء) by relying on students› imaginations. Furthermore, through audio-visual media, students can get new experiences that directly touch the motivation to learn Arabic, audiovisual media in Arabic is also known as al-wasa›il al-sam›iyyah wa al-basariyyah (وسائل السمعية والبصرية). This type of research is library research (Library Research). This research is qualitative in nature because the object of research is in the form of learning media which is explained with descriptions of words so that it can be understood easily. Learning media are used in order to improve or enhance the quality of the teaching and learning process. With this media, it is hoped that the learning atmosphere will not be boring and become more interesting so that it can foster student interest in learning Arabic lessons and more importantly the achievement of the objectives of teaching and learning activities and the curriculum.